2020
DOI: 10.4054/demres.2020.43.15
|View full text |Cite
|
Sign up to set email alerts
|

Trends in living arrangements and their impact on the mortality of older adults: Belgium 1991‒2012

Abstract: This article is dedicated to our colleague and friend Luc Dal, who passed away 3 November 2019. For more than 25 years, Luc made a significant contribution to our research by managing crucial administrative and statistical databases pertaining to the demographic characteristics of the Belgian population over the last several decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…For example, compared with those who maintained their partnership, a higher proportion of females was notable in groups where participants were living alone at follow-up. This is consistent with existing literature on demographic trends in aging populations—older women are more likely to be widowed and living alone (e.g., Bolina et al, 2021; Poulain et al, 2020). Thus, preventive healthcare and policy including bereavement care require attention toward gender perspectives.…”
Section: Discussionsupporting
confidence: 91%
“…For example, compared with those who maintained their partnership, a higher proportion of females was notable in groups where participants were living alone at follow-up. This is consistent with existing literature on demographic trends in aging populations—older women are more likely to be widowed and living alone (e.g., Bolina et al, 2021; Poulain et al, 2020). Thus, preventive healthcare and policy including bereavement care require attention toward gender perspectives.…”
Section: Discussionsupporting
confidence: 91%
“…However, the sex differential in mortality has been decreasing and this is considered likely to continue, to some extent, in the future. The resulting changes in the household structures of the elderly population seen in our microsimulation are in agreement with existing studies of past and future trends in the living arrangements and mortality of older adults [41,42].…”
Section: Discussionsupporting
confidence: 88%
“…Living in nursing homes has been found to be more acceptable in Nordic countries over time. A Swedish study found that the percentage of older adults living in collective increased sharply during the early 1990s, it then stabilized at the beginning of the 21st century and subsequently decreased after 10 years [38]. Berete and colleagues [39] suggested that among Belgian sample aged 65 and over who resided at home, 1.5% of them admitted to nursing homes in 2013 and 6.0% in 2019.…”
Section: Changing Patterns Of Living Arrangements Among Older Adultsmentioning
confidence: 99%